DESAIN DAN ANALISIS THERMAL PADA ELECTRIC VEHICLE (EV) HOME CHARGER 7,4 KW MENGGUNAKAN PENDEKATAN COMPUTATIONAL FLUID DYNAMIC (CFD) - Putra, Yoga Anggara; Hilmy, Fuad; Sulistyo, Raka Mahendra; Saleh, Arif Rahman (ELEMEN : JURNAL TEKNIK MESIN, 2024)
This research aims to design the EV Home Charger design with a CFD approach to analyze the heat transfer in the EV Home Charger casing using CAE software. The EV Home Charger design made in this research uses polycarbonate as the main material and provides several variations such as without a cooling fan and with a cooling fan. The results of this study show that the temperature generated by the EV Home Charger design without a fan has a higher temperature of 42.94℃, the EV Home Charger with a fan speed of 8 m/s is 40.85℃ with a percentage decrease in temperature of 5%. While the electric power consumed by the EV Home Charger without a fan has a higher power consumption of 68.79 watts and the EV Home Charger with an 8 m/s fan requires 61.93 watts of electric power, so it has a percentage of power reduction of 10%.